Analisa Efektivitas sistem Adaptive Defense Schemes (ADS) dengan teknologi 4.0 dalam Meningkatkan Keandalan Sistem Transmisi Tenaga Listrik Kalimantan - Nugraha, Arma Perwira; Irawan, Mohammad Isa (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The disruption of the electricity transmission system can lead to a total blackout, resulting in losses for both customers and PT PLN (Persero) UIP3B Kalimantan company. The vulnerability map of the Kalimantan interconnection system indicates that the Barikin - Tanjung Line is particularly vulnerable due to this transmission line is a crucial junction connecting major power plants to the transmission lines of South Kalimantan, Central Kalimantan, and East Kalimantan. Adaptive Defense Schemes (ADS) is an adaptive protection system that dynamically implements load shedding to reduce the risk of blackouts. ADS employs a Technology 4.0 system that integrates SCADA, protection, and IT systems, necessitating substantial costs. The effectiveness of ADS is assessed using ARIMA forecasting. Research result shows that ADS implementation reducing total disturbance as much as 77%, disturbance duration 68%, and ENS 65%. The result of ADS implementation impact in financial sector shows the reduction of 65% of company potential loss in effect of disturbance in transmission system, and also in the period of 2023 – 2026 where the ADS is still implemented, then the company could reduce 60% of its potential loss because of the disturbance in the transmission system